Mutu Fisik Makanan Pendamping ASI dari Bubuk Kedelai dan Kulit Buah Naga - Zora Olivia; Arinda Lironika Suryana; Nita Maria Rosiana (Puslitbang Sinergis Asa Professional, 2023)
Infants can be given complementary food to fulfil their nutritional needs at aged 6-24 months to prevent infants from malnutrition. A mixture of various ingredients in complementary foods can be made to obtain products with high nutritional value with quality that meets the requirements. In addition to nutritional quality, there are physical qualities that must be metIn addition to nutritional quality, there are physical qualities that must be met. The aim of this study was to determine the effect of the ingredient formulation on the physical properties of the complementary foods made from soybeans and dragon fruit peels. The samples used were MP_ASI products with various treatments of soybean powder and powdered milk (1:1; 5:9; 9:5). The physical properties test included kamba density analysis, brewing test, rehydration time and solubility. The results of the data were analyzed using the SPSS ANOVA test. The results showed that the ratio of soy powder and milk powder had a significant effect on the rehidration time (p=0,007) and brew analysis(p=0,03), but no significant effect on the bulk density and solubility(p>0,05). Soybean powder and dragon fruit peel extract can be ingredients for complementary food but other ingredients need to be added to increase the bulk density